Saxagliptin and Tadalafil Differentially Alter Cyclic Guanosine Monophosphate (cGMP) Signaling and Left Ventricular Function in Aortic‐Banded Mini‐Swine. Issue 4 (April 2016) - Hiemstra, Jessica A.; Lee, Dong I.; Chakir, Khalid; Gutiérrez‐Aguilar, Manuel; Marshall, Kurt D.; Zgoda, Pamela J.; Cruz Rivera, Noelany; Dozier, Daniel G.; Ferguson, Brian S.; Heublein, Denise M.; Burnett, John C.; Scherf, Carolin; et al.
Abstract : Background: Cyclic guanosine monophosphate‐protein kinase G‐phosphodiesterase 5 signaling may be disturbed in heart failure (HF) with preserved ejection fraction, contributing to cardiac remodeling and dysfunction. The purpose of this study was to manipulate cyclic guanosine monophosphate signaling using the dipeptidyl‐peptidase 4 inhibitor saxagliptin and phosphodiesterase 5 inhibitor tadalafil. We hypothesized that preservation of cyclic guanosine monophosphate cGMP signaling would attenuate pathological cardiac remodeling and improve left ventricular (LV) function. Methods and Results: We assessed LV hypertrophy and function at the organ and cellular level in aortic‐banded pigs. Concentric hypertrophy was equal in all groups, but LV collagen deposition was increased in only HF animals. Prevention of fibrotic remodeling by saxagliptin and tadalafil was correlated with neuropeptide Y plasma levels. Saxagliptin better preserved integrated LV systolic and diastolic function by maintaining normal LV chamber volumes and contractility (end‐systolic pressure‐volume relationship, preload recruitable SW) while preventing changes to early/late diastolic longitudinal strain rate. Function was similar to the HF group in tadalafil‐treated animals including increased LV contractility, reduced chamber volume, and decreased longitudinal, circumferential, and radial mechanics. Saxagliptin and tadalafil prevented a negative cardiomyocyte shortening‐frequency relationship observed in HF animals. Saxagliptin increased phosphodiesterase 5 activity while tadalafil increased cyclic guanosine monophosphate levels; however, neither drug increased downstream PKG activity. Early mitochondrial dysfunction, evident as decreased calcium‐retention capacity and Complex II‐dependent respiratory control, was present in both HF and tadalafil‐treated animals. Conclusions: Both saxagliptin and tadalafil prevented increased LV collagen deposition in a manner related to the attenuation of increased plasma neuropeptide Y levels. Saxagliptin appears superior for treating heart failure with preserved ejection fraction, considering its comprehensive effects on integrated LV systolic and diastolic function.